Classification of trophic state through species diversity and abundance of indicative rotifers in the surface waters of Lake Danao, ormoc City, Leyte, Philippines - Leseguis, Kimverly T. (2022)
Many studies have tried using rotifers as bioindicators of lakes' trophic status including the Brachionus: Trichocerca ratio (QB/T). This study attempts to determine the trophic state of Lake Danao in Ormoc City based on the abundance and diversity of indicative rotifers and the QB/T ratio. Five sampling stations were selected as representatives of the whole lake. Surface water samples (n=6 per station) were collected bimonthly via vertical towing from August, September, and December 2021 to January and February 2022. Nine rotifer species were identified from the samples wherein five of which were new records for Lake Danao.Keratella cf. tropica (464 indiv/l) and Polyarthra cf. vulgaris (159 indiv/L) were the most abundant, both of which are euthrophic forms. The mean QB/T value in Lake Danao was 1.01, classifying it as mesotrophic. The lake's mean levels of chl a concentration (3.69 ug/L) and transparency (4.15 m) were also mesotrophic. Pearson correlation showed that the monthly changes in the rotifer population were related to phosphates, nitrites, TDS, water transparency, DO, and conductivity of the lake. Also, based on the monthly averages of temperature, pH, DO, nitrates, phosphates, TDS, and nitrites, Lake Danao can still be a viable source of water supply under treatment. The dynamics of the rotiferan community structure through time could be attributed to the changing water parameters and trophic status of the lake. Eutropication has a major impact on mesotrophic lakes, therefore activities that may lead to nutrient enrichment of the water should be closely monitored.